1974
DOI: 10.1073/pnas.71.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Height for the Exchange Reaction F + HF → FH + F

Abstract: There exists a body of conflicting data as to the existence or nonexistence of FHF, ClHCI, BrHBr, and IHI as chemically bound molecular species. Ab initio quantum mechanical electronic structure calculations are presented which predict linear symmetric FHF to be unstable. The barrier height for the F + HF exchange reaction is suggested to be no less than 18 kcal/mol, much larger than expected either intuitively or on the basis of certain experiments on related systems. The expected reliability of the calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…We would expect to see manifestations of CSB on reactivity for cases that involve cleavage of CS bonds. Our studies [81] showed that one of these manifestations is the computational [82][83][84][85][86] and experimental [87] results that halogen transfer reactions (and especially of fluorine), Eq. (13a), have much larger barriers (by >20 kcal/mol for X¼F) than the corresponding hydrogen transfer processes, Eq.…”
Section: Atom Transfer Reactivity As Means Of Experimental Quantificamentioning
confidence: 69%
“…We would expect to see manifestations of CSB on reactivity for cases that involve cleavage of CS bonds. Our studies [81] showed that one of these manifestations is the computational [82][83][84][85][86] and experimental [87] results that halogen transfer reactions (and especially of fluorine), Eq. (13a), have much larger barriers (by >20 kcal/mol for X¼F) than the corresponding hydrogen transfer processes, Eq.…”
Section: Atom Transfer Reactivity As Means Of Experimental Quantificamentioning
confidence: 69%
“…The barrier calculated by the model for X ) X′ ) F is also in good agreement with the datum of Schaefer et al is 23.9 kcal/ mol. 35 In fact, the barriers in Tables 2 and 3 enable us to assess the model equation's ability to predict trends along a row of the priodic table. Thus, eq 22 predicts, in accord with the results of CCSD(T), that in each row the identity barrier is generally larger for the more electronegative groups, X and X′ (compare, e.g., the barriers for X ) F vs CH 3 , etc).…”
Section: Discussionmentioning
confidence: 99%
“…-> F + FO +(101) F + F20 -F2 + FO(102) FO + FO -02 + 2F(88) F + F + M-*"F2 + M(97) An activation energy of 14.3 ± 1.5 kcal for reaction 102 was determined from the photochemical investigation,125 while the results of the thermal study126 gave k102 = 5.1 X 101°e xp[-(13.7 ± 1.0) X 103/fi7] cm3 mol-1 s-1.…”
mentioning
confidence: 99%